ANALYTICAL STUDY ON IMPACT OF PARENTAL SUBSTANCE ABUSE ON CHILDREN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Drug abuse is the world's leading cause of death and a global epidemic. Per year, millions of deaths and millions of new HIV cases are caused by the worldwide issue of addiction and substance misuse. India has seen an increasing trend in drug dependency in recent years. In India, tobacco, cannabis and opiates are the most popular drug users. The usage of drugs, whether lawful or illegal, induces substantial individual health issues. We investigated (1) variations in the prevalence of emotional and behavioural disturbances over time between children of alcohol-free parents, parents with lesser issues with alcohol, and parents with serious problems with alcoholic substances.